Clinical features, diagnosis and therapeutic strategies in pediatric multiple sclerosis. (January 2017) - Ochi, Hirofumi
Abstract: Multiple sclerosis (MS) is a complex immune‐mediated disease characterized by recurrent demyelinating episodes of the central nervous system, which typically occurs in young adults. It is the most common disabling neurological disease of young people; however, pediatric MS, defined as onset of MS before the age of 18 years, has been increasingly recognized worldwide in the past two decades. Pediatric MS might represent up to 10% of all patients with MS. As in adults, the diagnosis of pediatric MS rests on the demonstration of dissemination of lesions in both space and time, and the exclusion of alternative diagnosis. However, it can be more difficult to distinguish MS accurately from other conditions in children compared with the adult population, because there is considerable overlapping of clinical and magnetic resonance imaging features between pediatric MS and other acquired demyelinating disorders of the central nervous system. In view of therapeutic strategies, although interferon‐beta and glatiramer acetate are the most commonly used disease‐modifying drugs for pediatric MS so far, none of the current available disease‐modifying drugs were tested in pediatric MS by randomized controlled trials, and thus there is limited information regarding the efficacy and safety. The present review article describes the epidemiology, clinical features, consensus definition and treatment strategy of pediatric MS.